PENINGKATAN KETERAMPILAN MENYUSUN TEKS FABEL MELALUI PEMBELAJARAN KOOPERATIF MODEL LINGKARAN IMAJINASI DAN MEDIA GAMBAR PADA SISWA KELAS VIII A SMP PATRA DHARMA 2 BALIKPAPAN TAHUN AJARAN 2015/2016 - Rika Afriani (Kantor Bahasa Kalimantan Timur, 2017)
The purpose of this research was to describe student’s skill enhancement in writing fable texts using cooperative learning model of imagination circles and pictures in SMP Patra Dharma 2 Balikpapan, VIII A students, school year 2015/2016. It was a two cycle classroom action research. It used fable assessment rubric sheets, participant observation sheets, lesson plan observation sheet, teaching activity observation sheet, student activities’ observation sheet, and field notes. The result showed that the average value of pre-cycle was 69. It revealed that it did not reach the minimum mastery standard in fable text writing which were 78. Thirteen out of 36 students got minimum scores. In the first cycle after the action given, thirty one students reached the minimum mastery standard. Their average value was 83. The average value of the second cycle was 92. It showed a very satisfactory result with 100% completeness percentage. It concluded that the cooperative learning model implementation of circle imagination and pictures as instructional media could increase the ability of VIII-A students of SMP Patra Dharma 2 Balikpapan school year 2015/2016 in writing fable text.